This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
2 5 × 3 6 = 5 2 × 6 2 = ( 5 × 6 ) 2 = 3 0 2 = 9 0 0
This will take more than 2 sec !
Simply multiply to obtain 9 0 0 .
25=5^2. 36=6^2 =(5*6)^2 = 30^2 = 900
Replace 2 5 = 4 1 0 0 , so now we have 1 0 0 × 4 3 6 , which is equal to 9 0 0
2 5 × 3 6 = 3 0 × 3 0 = 9 0 0
It can be solved the other way that 36 × 25 = 36 × 100/4 = 9 × 100 = 900
I did it:
If 2 5 × 3 6 = 2 5 × 9 × 4 I have 1 0 0 × 9 = 9 0 0 !
Problem Loading...
Note Loading...
Set Loading...
3600 divided by 4 =